PsoBarrier EU study: a Multicentre, Cross-sectional Survey Investigating the Quality of Psoriasis Care in Four European Countries - Anna Langenbruch; Nicole Mohr; Valerie Andrees; Ihno Kessens; Adam Reich; Magdalena Czarnecka-Operacz; Luis Puig; Esteban Dauden; Lars Iversen; Matthias Augustin (Medical Journals Sweden, 2023)
Enhanced treatment options for psoriasis and growing use of guidelines increased the potential to better quality of psoriasis care in Europe. The aim of the PsoBarrier EU study is to compare the quality and processes of psoriasis care in four European countries with different healthcare systems, based on validated quality indicators. This cross-sectional survey was conducted in dermatology centres in Denmark, Germany, Poland and Spain on 1,304 patients, using standardized patient and physician questionnaires. Measured by quality of psoriasis care indicators, patients in Poland had the most critical outcomes, such as the highest disease severity (Psoriasis Area and Severity Index; PASI) and lowest health-related quality of life (Dermatology Life Quality Index; DLQI). This indicates differences in psoriasis care, with Polish participants experiencing more severe psoriasis and its consequences. Differences in the healthcare systems, which create barriers to accessing treatments, could explain variations in quality of care.